Flexural analysis of concrete beams longitudinally reinforced with GFRP bars using discrete element model - Suki, Nauwal (2011)
This paper presents experimental and analytical study related to the flexural behavior of concrete beams longitudinally reinforced with GFRP bars. The specimens consist of simply supported reinforced concrete beams with two point load. Totally 16 concrete beams includes 8 beams reinforced with steel and 8 beams reinforced with GFRP bars were tested to failure. Flexural capacity of the beam was observed experimentally and analytically. A computer program of cross sectional analysis using discrete element model was developed in this study to determine the flexural capacity of the beams. In addition, available stress-strain model proposed by the other researchers was used in order to simulate the behavior of material in calculation process. Finally, the flexural capacity obtained from analytical calculation was compared to that obtained from the test in term of moment-curvature curves and load deflection curves. The results show that beam reinforced with GFRP experienced larger ultimate load and larger deflection at same load level compared to beam reinforced with steel.